Challenges contributing to disrupted transition from paediatric to adult diabetes care in young adults with Type 1 diabetes. Issue 12 (26th May 2014) - Pyatak, E. A.; Sequeira, P. A.; Whittemore, R.; Vigen, C. P.; Peters, A. L.; Weigensberg, M. J.
Abstract Aim To examine challenges contributing to disruptions in care during the transition from paediatric to adult care among young adults with Type 1 diabetes who are primarily in ethnic minority groups and have low socio‐economic status. Methods Participants (n = 20) were newly enrolled patients in a transition clinic for young adults with Type 1 diabetes with a history of loss to medical follow‐up. Participants completed qualitative semi‐structured interviews detailing their transition experiences in addition to demographic, HbA1c and psychosocial measures. Descriptive statistics were completed for quantitative data, and narrative thematic analysis of interviews was used to identify common themes. A mixed‐method analysis was used to identify the associations between stressors identified in interviews and clinical and psychosocial variables. Results Three categories of challenges contributing to loss to follow‐up were identified: psychosocial challenges, health provider and health system challenges and developmental challenges. Participants experienced a high degree of stressful life circumstances which were associated with higher HbA1c (r = 0.60, P = 0.005), longer duration of loss to follow‐up (r = 0.51, P = 0.02), greater emergency department utilization (r = 0.45, P = 0.05), and lower life satisfaction (r = ‐0.62, P = 0.003). Conclusions A confluence of challenges, including stressful life circumstances, healthcare system barriers and the developmental trajectory of young adulthood, contributes to a high risk of loss to follow‐up and poor health in this population of young adults with Type 1 diabetes. An integrated approach to transition addressing medical and psychosocial needs may facilitate improved follow‐up and health outcomes in clinical settings.